2014
DOI: 10.3177/jnsv.60.357
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Bevacizumab and Acyclic Retinoid Inhibits the Growth of Hepatocellular Carcinoma Xenografts

Abstract: SummaryThe prognosis of patients with hepatocellular carcinoma (HCC) is poor and the development of effective treatments for this malignancy, including combination chemotherapy, is required. This study examined the possible combined inhibitory effects of bevacizumab, an anti-vascular endothelial growth factor monoclonal antibody, and acyclic retinoid (ACR), which can prevent the development of HCC, on the growth of Huh7 human HCC cells. Xenograft tumors were produced by subcutaneously injecting Huh7 cells into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several preclinical studies did suggest that the use of bevacizumab in combination with other agents may be a choice for HCC treatment. 64 We found that calcitriol inhibited the growth of gastric cancer cells by inducing Dicer expression, 65 however a suitable concentration of calcitriol should be assessed and validated preclinically in HCC xenografts.…”
Section: Discussionmentioning
confidence: 91%
“…Several preclinical studies did suggest that the use of bevacizumab in combination with other agents may be a choice for HCC treatment. 64 We found that calcitriol inhibited the growth of gastric cancer cells by inducing Dicer expression, 65 however a suitable concentration of calcitriol should be assessed and validated preclinically in HCC xenografts.…”
Section: Discussionmentioning
confidence: 91%
“…ACR and ARB have been demonstrated to exert multiple pharmacological activities for efficiently preventing hepatocarcinogenesis. Similar to ARB, ACR also commonly exerts synergistic effects in combination with other clinically available drugs, including interferon-β, valproic acid, vitamin K2, trastuzumab, and bevacizumab [ 48 51 ]. In addition to these agents, recent xenograft analysis has demonstrated that branched-chain amino acids (BCAA) may also be used as a candidate partner for peretinoin-based cocktail therapy against HCC [ 35 ].…”
Section: Discussionmentioning
confidence: 99%